Psychosocial and stress-related risk factors for abnormal menstrual cycle pattern among adolescent girls: A case-control study - Nishu Jha; Ajeet Singh Bhadoria; Yogesh Bahurupi; Kanchan Gawande; Bhavna Jain; Jaya Chaturvedi; Surekha Kishore (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Menstruation is a normal physiological process among reproductive age group females. Although some of them show the abnormal menstrual pattern, which is influenced by several factors, including sociodemographic status, psychosocial stress, improper sleep level, etc. The identification of these risk factors associated with abnormal menstrual patterns may permit risk stratification among adolescent girls. This study was planned to determine various factors which depict menstrual cycle pattern among adolescent girls in urban India. MATERIALS AND METHODS: A school-based case-control study was carried out in urban India from May to December 2019. Urban locality and schools were randomly selected, and data were collected in two phases. Adolescent girls in the age group of 10-19 years studying in government and private (both Hindi medium and English medium) schools of urban India were screened for the abnormal menstrual pattern. Equal numbers of age-matched controls were also enrolled. Data were collected with the help of self-administered predesigned pretested semi-structured questionnaire. Chi-square test, Fisher's exact test, unpaired t-test, and McNemar tests were used to analyze data using SPSS version 23.0. RESULTS: A total of 100 cases and 100 age-matched controls (mean age 14.8 ± 1.5 years) were included in the study, almost half of the cases and controls have normative menarche. Improper sleep patterns increased stress levels, and low education status of mothers show statistically significant (P = 0.047) association with abnormal menstrual patterns. CONCLUSION: More stress, improper sleep levels, and low education status of mothers among school-going adolescent girls were strongly associated with abnormal menstrual patterns with more symptoms during menstruation.